Development of soybean oil‐based aqueous polyurethanes and the effect of hydroxyl value on its properties. (22nd April 2022) - Lou, Wenxue; Dai, Zhuding; Jiang, Pingping; Zhang, Pingbo; Bao, Yanmin; Gao, Xuewen; Xia, Jialiang; Haryono, Agus
Abstract: A series of soybean oil‐based polyols were synthesized via the reaction between epoxidized soybean oil and 1, 3‐propanediol, trimethylolpropane and xylitol, respectively. The aqueous polyurethanes were synthesized by prepared soybean oil‐based polyols. The effect of hydroxyl value of soybean oil‐based polyols on the mechanical, thermal, hydrophobic properties of the aqueous polyurethane films were also investigated. The results showed that the OH value of polyol increased, the T g of aqueous polyurethane films increased from 30.04 to 88.28 °C and the water contact angle of materials improved from 80.80° to 98.20°. Besides, water absorption reduced from 40.25% to 2.40%. Also, all samples were placed in the 1 wt% sodium hydroxide solution at 45 °C to test the degradation behaviors. After 24 h, the results demonstrated that aqueous polyurethane synthesized by the highest hydroxyl value(251.00mgKOH/g)polyol had the lowest degradation rate(7.10%). Finally, the mechanical properties and morphology of the aqueous polyurethane film after degradation were investigated, which proved that the hydroxyl value affected the mechanical properties and morphology of the aqueous polyurethane film after degradation.